THERMOMAGNETIC MEASUREMENTS OF SOIL IRON MINERALS: THE ROLE OF ORGANIC CARBON - Hanesch M.; Stanjek H.; Petersen N. (My University, 2006)
Thermomagnetic measurements, particularly measurements of the Curie or Néel temperature, are often used to identify magnetic minerals in rocks or sediments. In many samples it is impossible to determine the Curie or Néel temperature as mineral changes occur during heating. Especially in soils or sediments, iron (hydr)oxides may be transformed to ferrimagnetic iron oxides. In this study we analysed the thermomagnetic behaviour of some natural and synthetic iron minerals: goethite, haematite, ferrihydrite, lepidocrocite and siderite. The change of magnetization. © 2006 The Authors Journal compilation © 2006 RAS.
Keywords: CURIE TEMPERATURE; IRON HYDROXIDES; NÉEL TEMPERATURE; SOIL MAGNETISM